The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/acel.13105
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness in community‐dwelling older adults is linked to dietary intake, gut microbiota, and metabolomic signatures

Abstract: When humans age, changes in body composition arise along with lifestyle‐associated disorders influencing fitness and physical decline. Here we provide a comprehensive view of dietary intake, physical activity, gut microbiota (GM), and host metabolome in relation to physical fitness of 207 community‐dwelling subjects aged +65 years. Stratification on anthropometric/body composition/physical performance measurements (ABPm) variables identified two phenotypes (high/low‐fitness) clearly linked to dietary intake, p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 37 publications
2
61
0
1
Order By: Relevance
“…Importantly, analysis of previously published 16S rRNA gene amplicon data [24], showed that the prokaryote community does not cluster in relation to blood triglyceride, nor VLDL cholesterol levels (Figure 1 (v) and 2 (v), p = > 0.05).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Importantly, analysis of previously published 16S rRNA gene amplicon data [24], showed that the prokaryote community does not cluster in relation to blood triglyceride, nor VLDL cholesterol levels (Figure 1 (v) and 2 (v), p = > 0.05).…”
Section: Resultsmentioning
confidence: 84%
“…Phenotypic and blood clinical parameters, stool and plasma metabolome, 3-days weighted dietary records, and 16S rRNA gene amplicon sequencing have been reported previously [24] but here, we integrated these data with gut mycobiome compositional data.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA concentration was measured using Qubit dsDNA BR Assay Kit (Thermo Fisher Scientific Inc., Waltham, USA). The gut microbiota composition of 27 subjects was successfully analyzed by 16S ribosomal RNA (rRNA) gene amplicon sequencing of the V3 region on the Illumina NextSeq platform (Illumina Inc.) with the Mid Output Kit v2 (300 cycles) as previously described ( 20 ). The raw dataset containing pair-ended reads with matching quality scores were fused and clipped in the USEARCH pipeline using fastq_mergepairs and fastq_filter scripts.…”
Section: Methodsmentioning
confidence: 99%
“…Following the other approach, Castro-Mejía et al [ 88 ] classified individuals into two groups (high physical fitness and low physical fitness) according to their performance in the 30 s Chairstand test, BMI and percentage of leg-soft-tissue fat. Multivariant analysis identified a group of variables which can accurately discriminate between groups (dietary sources, plasma and fecal metabolites, microbial taxa, biochemical parameters and steps per day), including higher abundance of Bifidobacterium adolescentis and several species of Chritensenella genus in high fitness group, whereas the low fitness group microbiota was enriched in Enterobacterales .…”
Section: Gut Microbiota Targeted Interventions In the Elderlymentioning
confidence: 99%